REVIEW of the scientific article by Karyna Poltavets "Business Models of Vertical Integration in the Beauty Industry in the United States: Analysis of Economic Efficiency" - Pereshliuga, Kseniia (Global Prosperity, 2025)
REVIEW of the scientific article by Karyna Poltavets "Business Models of Vertical Integration in the Beauty Industry in the United States: Analysis of Economic Efficiency"